Fiscal Policies in EMU Countries: Strategies and Empirical Evidence. Issue 1 (21st March 2016) - Magazzino, Cosimo; Forte, Francesco
Abstract : Purpose: The aim of the paper is to evaluate fiscal adjustments occurred in EMU countries in the last 35 years, and their consequences on the economic growth process, using the mean group (MG) estimators. Design/methodology/approach: Our emphasis is put on the effects of different composition of fiscal stimuli and consolidations. We compare the effects on the economic growth rate of different compositions of major fiscal changes. We use a cyclically adjusted value of the fiscal variables to leave aside variations of the fiscal variables induced by business cycle fluctuations. Findings: Our empirical research of the effects of large changes in fiscal policy, both in case of a fiscal consolidation and of fiscal stimulus in the eighteen EMU countries from 1980 to 2015, shows that adjustments by cutting current expenditures, rather than by tax increases are more likely to boost economic growth. It also shows that cuts of investment expenditures may reduce GDP growth. During fiscal stimulus episodes, tax cuts and public investments are more likely to increase growth than current public expenditure increases. Originality/value: This is the first study devoted to the EMU countries. It should be underlined that the results obtained as for EMU countries are not necessarily applicable to other countries, as the different government size as well as different market institutions may influence the results.